Selective solvothermal extraction of tetrabromobisphenol A to promote plastic recycling - Paavo Auvinen; Ville H. Nissinen; Erno Karjalainen; Kirsi Korpijärvi; Eerika Olkkonen; Krista Grönlund; Ilkka Rytöluoto; Lauri Kuutti; Mika Suvanto; Janne Jänis; Jarkko J. Saarinen (Chemical Engineering Journal Advances)
Removal of brominated flame retardants (BFRs) is imperative for increasing the recycling rate of hazardous plastic waste. In mechanical recycling, BFRs should be removed without damaging the surrounding polymer matrix, but economically viable processes under mild conditions are still rare. In this study, tetrabromobisphenol A (TBBPA) was solvothermally extracted from a compounded high-impact polystyrene (HIPS, 2500 ppm Br) model sample in an autoclave using mixtures of water, isopropanol (IPA) and NaOH as solvents. Removal of total elemental bromine was analyzed with X-ray fluorescence (XRF), whereas the removal of TBBPA and other plastic additives was evaluated with direct insertion probe mass spectrometry (DIP-MS). IPA/NaOH extraction provided efficient bromine removal, but it also extracted plenty of other plastic additives, including phenolic stabilizers Irganox 1076 and Cyasorb UV-2908. The inclusion of water in the IPA/NaOH mixture shifted the extraction selectivity towards TBBPA, leaving most of the other additives unaffected. Furthermore, H2O/IPA/NaOH was found to be equally effective in removing TBBPA from the samples with bromine concentrations an order of magnitude higher (25,000 ppm). Yet, larger plastic particle size hindered the extraction efficiency. 1H NMR and size exclusion chromatography confirmed that the HIPS matrix was left unaffected after all the studied extractions. Additionally, DIP-MS was found to be a valuable characterization method for assessing the removal and decomposition of various additives from solid plastic samples with minimal sample preparation. Overall, the results presented herein offer a target-selective extraction processes under relatively mild conditions for further advancing the mechanical recycling of plastics.